Reader answerability in the genre "Readers Letters "in the press: analysis of discursive polemics from a Bakhtinian perspective - Simone Ribeiro de Avila Veloso (Filologia e Linguística Portuguesa, 2013)
This paper aims to present part of a research, developed at a post-doctoral level, whose purpose is to investigate the answerability of the reader in the genre “readers letters” in concrete utterances published in the newspapers Folha de S. Paulo and O Estado de S. Paulo and Veja magazine. The study considers speciﬁcally the refracted speeches marked by open and veiled polemics, achieved by the readers of each of the media, in view of the architectonics constitutive of concrete utterances. The analytical focus will center on how readers polemize with speeches representative of the established political spheres, observing a context of political transition characterized by the last military government. With this end in view, we selected letters published, concurrently in those three vehicles in the ﬁrst half of February 1980, in order to observe the events that were reported in the three media corporations.